THE EFFECT OF USING COPPER CATALYTIC CONVERTER ON EXHAUST GAS EMISSIONS OF URBAN CAR ANTASARI EVO I - Ramadhan, Muhammad Nizar; Ghofur, Abdul; Alimuddin, Ahmad Noor; Azlan, Mohd; Setiawan, Bayu (Universitas Negeri Malang, 2024)
The increasing growth of motorized vehicles as a means of transportation has an impact on increasing air pollution. Air pollution from motorized vehicles that exceeds the threshold will cause health problems. A catalytic converter is one of the tools used to reduce exhaust gas that works by converting toxic compounds in exhaust gas into less toxic or non-toxic substances. The application of catalytic converters in motorized vehicles has many variations based on the problems and variations in their solutions. The purpose of this study was to determine the effect of using a catalytic converter with a 1 mm thick copper plate material on exhaust emissions of CO2, CO and HC in the Antasari Evo I Urban Car. Testing was carried out by comparing exhaust emissions produced by standard exhaust and exhaust installed with a catalytic converter based on variations in idle engine speed, 2000 rpm, 2500 rpm, and 3000 rpm. From the research results, it was found that the effect of using a copper plate catalytic converter placed on the exhaust gas channel can reduce the highest CO2 emission concentration by 40%, the highest CO emission concentration by 87%, and the highest HC emission concentration by 62%.